Short-term outcome of metabolic surgery versus intensive medical therapy among obese type 2 diabetics: a quasi-experimental study - Zahra Raza; Muhammad Burhan Ul Haq; Tashfeen Imtiaz; Muhammad Adnan Khokhar; Aatif Inam (Journal of the Pakistan Medical Association)
Objective: To compare the short-term outcomes of metabolic surgery and intensive medical therapy in the management of diabetes mellitus among obese persons with type 2 diabetes mellitus.